Caries Progression Rates Revisited: A Systematic Review. (July 2019) - Hummel, R.; Akveld, N.A.E.; Bruers, J.J.M.; van der Sanden, W.J.M.; Su, N.; van der Heijden, G.J.M.G.
Caries progression seems to follow universal, predictable rates, depending largely on the caries severity in populations: the higher the caries severity, the higher the progression rates. Quantification of these rates would allow prediction of future caries increments. Our aim was to describe caries progression rates in the primary and permanent dentition in Western populations (not in lesions) of children and adolescents. Therefore, we systematically searched MEDLINE-PubMed, Embase, CINAHL, and the Cochrane library for studies reporting caries progression data. Eligibility criteria were reporting empirical data from at least 2 full-mouth dental caries examinations in a closed cohort during a follow-up of at least 3 y, a first examination after 1974, a second examination before the age of 22 y, caries assessed as dentine caries (d3 /D3 ), and caries reported in dmfs/DMFS (decayed, missing, and filled surfaces), dmft/DMFT (decayed, missing, and filled teeth), or caries-free participants. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement, we described the results for the primary and permanent dentition in a systematic review, performed a meta-analysis for the caries incidence rate in the permanent dentition, and conducted multivariate, hierarchical meta-regression analyses for the caries incidence rate and the increments in DMFS and DMFT. Of the 6, 343 unique studies retrieved, 43 studies (56, 376 participants) were included for systematic review and 32 for meta-analyses (39, 429 participants). The annual decline in caries-free children in the permanent dentition ranged from 0.8% to 10.2%. The annual increment ranged from 0.07 to 1.77 in DMFS and from 0.06 to 0.73 in DMFT. The pooled caries incidence rate was 0.11 (0.09–0.13) per person-year at risk. Meta-regression analyses showed that the methods of individual studies influenced pooled caries incidence rates and increments in DMFS and DMFT. This should be taken into account in planning and evaluation of oral health care services. However, the caries incidence rate is promising for prediction of future caries increments in populations.